Algorithms for rapid memorization of musical notation through associative thinking in the methodology of early music education - Bohancha, Maryna (Педагогічна Академія: наукові записки, 2026)
The relevance of the study is determined by the necessity to improve the effectiveness of early music education under conditions of increasing demands on the speed of musical notation acquisition, the development of musical memory, and the formation of stable performance skills in primary school children. In contemporary pedagogical practice, mechanical repetition of notation material is becoming increasingly insufficient, which actualizes the need for methods aimed at activating figurative, emotional, and multisensory perception of music. Particular significance is attached to associative thinking as a tool for forming stable cognitive connections between sound, rhythm, movement, emotional imagery, and notation symbols. The purpose of the article is defined as the development and theoretical-methodological substantiation of approaches to the use of associative thinking for accelerating the memorization of musical notation within the system of early music education. Methods. The study employed methods of theoretical generalization, analysis and synthesis of scientific sources, a logical-analytical approach, and the method of pedagogical interpretation to identify the functional capabilities of associative algorithms in music education. Results. The pedagogical significance of associative thinking in the formation of beginner learners’ musical memory has been investigated. It has been revealed that the combination of visual, auditory, emotional, and motor associations increases the stability of memorization of musical material and improves the quality of its reproduction. Methodological approaches to integrating associative algorithms into the structure of early music education have been substantiated, particularly through rhythmic-motor synchronization, visual-structural modeling, and contextual interpretation of musical text. Key scientific and practical problems have been identified, including insufficient systematization of associative methods, cognitive overload of learners, instability of concentration, and limited adaptation of methods to the individual perceptual characteristics of children. Conclusions. It has been proven that the effectiveness of memorizing musical notation significantly increases through the combination of multisensory interaction, emotional engagement, and consistent organization of associative learning. Prospects for further research are associated with the development of adaptive music education models for different age groups, empirical verification of the effectiveness of associative algorithms, and investigation of the potential of digital interactive technologies in the development of musical memory.